2022
DOI: 10.3389/fnhum.2021.793952
|View full text |Cite
|
Sign up to set email alerts
|

Like/Dislike Prediction for Sport Shoes With Electroencephalography: An Application of Neuromarketing

Abstract: Neuromarketing is an emerging research field for prospective businesses on consumer’s preference. Consumer’s preference prediction based on electroencephalography (EEG) can reliably predict likes or dislikes of a product. However, the current EEG prediction and classification accuracy have yet to reach ideal level. In addition, it is still unclear how different brain region information and different features such as power spectral density, brain asymmetry, differential entropy, and Hjorth parameters affect the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
(45 reference statements)
0
14
0
1
Order By: Relevance
“…Cada una de dichas neuronas constituye un diminuto dipolo eléctrico, cuya polaridad depende de que el impulso a la célula sea inhibitorio o excitatorio (Ramos-Argüelles et al, 2009). Para poder recoger y registrar una señal de la actividad eléctrica en cada región cerebral a través de la superficie craneal se colocan electrodos que captan la diferencia de potencial entre ellos (Zeng et al, 2021). La EEG realiza el estudio y análisis de los campos eléctricos cerebrales (topografía, polaridad y su variación espacial temporal) mediante la amplificación de la diferencia de potencial entre los electrodos receptores de la señal.…”
Section: Electroencefalografía Y Emociones Humanasunclassified
“…Cada una de dichas neuronas constituye un diminuto dipolo eléctrico, cuya polaridad depende de que el impulso a la célula sea inhibitorio o excitatorio (Ramos-Argüelles et al, 2009). Para poder recoger y registrar una señal de la actividad eléctrica en cada región cerebral a través de la superficie craneal se colocan electrodos que captan la diferencia de potencial entre ellos (Zeng et al, 2021). La EEG realiza el estudio y análisis de los campos eléctricos cerebrales (topografía, polaridad y su variación espacial temporal) mediante la amplificación de la diferencia de potencial entre los electrodos receptores de la señal.…”
Section: Electroencefalografía Y Emociones Humanasunclassified
“…It is the most commonly used feature in Neuromarketing studies as presented in Table 4 . The asymmetry in EEG band power is an indicator of consumer preferences, which is why it is widely used in Neuromarketing [ 10 , 40 , 68 , 72 ]. To determine the power spectra of EEG sub-bands, firstly a Fast Fourier Transform (FFT) algorithm is used to calculate the Discrete Fourier Transform (DFT) of the EEG signal sequence as given by Eq.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Neuromarketing studies how people's brains react to particular ads, package designs, products, etc., using non-invasive brain-scanning techniques, such as EEG [ 8 10 ], functional magnetic resonance imaging (fMRI) [ 11 13 ], functional near-infrared spectroscopy (fNIRS) [ 14 , 15 ], etc. These neurophysiological data may now accurately represent customers' preferences, likes, and dislikes using modern feature extraction and classification algorithms [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2022), and beta (Boksem & Smidts, 2015; Zeng et al, 2022) frequencies are also correlated with preference judgments. According to Zeng et al (2022), preference indices based on brain asymmetries, such as the approach-withdrawal index, valence, choice index, and effort index, are also used to predict consumer preferences (Aldayel et al, 2021). According to Boksem and Smidts (2015), this method allows marketers to obtain information that cannot be reliably obtained using traditional methods with a relatively small sample size with a true predictive ability of commercial success.…”
Section: Introductionmentioning
confidence: 96%
“…However, some research has also shown that gamma (Ramsøy et al, 2018), theta (A. Wang et al, 2022), and beta (Boksem & Smidts, 2015; Zeng et al, 2022) frequencies are also correlated with preference judgments. According to Zeng et al (2022), preference indices based on brain asymmetries, such as the approach-withdrawal index, valence, choice index, and effort index, are also used to predict consumer preferences (Aldayel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%